Alpha-1-antitrypsin in human macrophages. Issue 9 (September 1981) - Isaacson, P; Jones, D B; Millward-Sadler, G H; Judd, M A; Payne, S
Abstract : Preliminary studies have suggested that alpha-1-antitrypsin (A1AT) is a useful immunohistochemical marker of histiocytes (monocytes/macrophages) and malignant tumours derived from them. To confirm the reliability of this marker a wide variety of benign and malignant lymphoreticular cells and tissues have been stained by the immunoperoxidase technique for A1AT and positive staining was found to be confined to histiocytes. Immunodiffusion, isotope labelling, and isoelectric focusing studies performed on cell lysates confirmed that the positive staining shown by monocytes and malignant histiocytes is due to the presence of A1AT identical with serum A1AT and that this material is synthesised by these cells rather than taken up from their environment. Positive immunoperoxidase staining for A1AT is thus a reliable marker of lymphoreticular neoplasms of true histiocytic origin.